Effect of cardiac rehabilitation on neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio in ST elevation myocardial infarction patients - Zengin, İsmet; Arı, Selma (The European Research Journal, 2019)
Objectives: Cardiac rehabilitation is known to have positive effects on the inflammatory processes. The neutrophil-to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR) were found to be indicative of inflammation. The purpose of this study is to determine the effects of cardiac rehabilitation on the NLR and PLR ratios of ST elevation myocardial infarction (STEMI) patients.Methods: The study includes 101 STEMI patients that underwent primary percutaneous coronary intervention (PCI). The patients were randomized into two groups: the cardiac rehabilitation group (CR group, n = 68), and the control group (n = 33). One month after primary PCI, cardiac rehabilitation was applied to CR group with cycle ergometer for 8 weeks (30 sessions). The NLR and PLR parameters were calculated from the complete blood count results from before and after the cardiac rehabilitation application for both groups.Results: When the baseline values of the two groups were evaluated, the hemoglobin value of the control group (13.10 ± 1.52 g/dL vs. 13.79 ± 1.26 g/dL; p = 0.03) and the PLR value of the CR group (122.50 ± 43.89 vs. 92.41 ± 23.70; p = 0.001) were significantly higher. The post-cardiac rehabilitation complete blood count parameters, and the NLR and PLR values were similar in both groups. The NLR (3.11 ± 1.95 vs 2.39 ± 1.03; p = 0.003) and PLR (122.50 ± 43.89 vs. 108.68 ± 41.83; p = 0.025) parameters significantly decreased after the cardiac rehabilitation application in the CR group, whereas there wasn't a change in the control group. Conclusion: It was found that cardiac rehabilitation applied in STEMI patients caused a significant decrease in NLR and PLR parameters, which are indicators of inflammation.